Effects of Dietary Interventions on Gut Microbiota in Humans and the Possible Impacts of Foods on Patients' Responses to Cancer Immunotherapy. Issue 4 (27th August 2020) - Wang, Li‐Shu; Mo, Yue Yang; Huang, Yi‐Wen; Echeveste, Carla Elena; Wang, Hsin‐Tzu; Chen, Jiali; Oshima, Kiyoko; Yearsley, Martha; Simal‐Gandaraf, Jesus; Battino, Maurizio; Xiao, Jianbo; Chen, Jiebiao; et al.
Abstract : The gut microbiota—the community of microorganisms in the gut—has been implicated in many physical and mental disorders in addition to intestinal diseases. Diets are the most studied and promising factors for altering it. Indeed, certain dietary interventions that increase fiber intake rapidly change levels of certain nutrients that can modify the composition of the microbiota, promoting richness and diversity. Recent intriguing evidence from several human clinical trials suggested that the composition and diversity of patients' gut microbiotas at baseline can influence their responses to cancer immunotherapy. If the factors that influence the gut microbiota were fully understood, it is conceivable that manipulating them could boost therapeutic responses in cancer patients. In this review, we investigate the possibility of using fruits, vegetables, or whole grains to enhance response to cancer therapies in humans, as current evidence suggests that these dietary components can manipulate and enhance diversity of the gut microbiota. Accordingly, dietary interventions with locally available fruits, vegetables, and whole grains might be an affordable and safe approach to enhancing the diversity of the gut microbiota before immunotherapy, in turn improving patients' responses to their treatments. GRAPHICAL ABSTRACT: